2018
DOI: 10.1007/s12070-018-1263-1
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Lateralization Training Effects on Binaural Interaction Component of Middle Latency Response in Children Suspected to Central Auditory Processing Disorder

Abstract: Many children with central auditory processing disorder (C)APD suffer from spatial processing disorder and benefit from binaural processing training including auditory lateralization training. There are subjective tests for evaluating auditory training effects in children with (C)APD but they rely on patient's attention and cooperation so there is a need for appropriate objective tests. The aim of present study was investigating effects of auditory lateralization training on binaural interaction component (BIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…After the presentation of each word, the person was asked to repeat the word. The total score for each spatial location was calculated in percentage [2]. Then participants were asked to complete the SHQ questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the presentation of each word, the person was asked to repeat the word. The total score for each spatial location was calculated in percentage [2]. Then participants were asked to complete the SHQ questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…The spatial hearing is the ability of the auditory system for detecting the direction of sound source [1] based on the monaural and binaural cues and helps us separate target speech from competing signals and improves the speechin-noise skill [2,3]. Spatial hearing defects might contribute to some disorders such as (central) auditory processing disorder ((C)APD) [1, 3,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that the MLR is modulated by differences in interaural time and intensity cues, which are important for sound localization and binaural fusion [ 29 ]. Furthermore, the MLR has been shown to be associated with the perceptual grouping of sounds, such as the segregation of speech from background noise [ 37 , 38 ]. However, the literature on the MLR in binaural hearing is limited, and more research is required to comprehend its role in binaural hearing.…”
Section: Introductionmentioning
confidence: 99%